Prevalence of Batrachochytrium dendrobatidis in Amphibians From 2000 to 2021: A Global Systematic Review and Meta-Analysis - Li, Zhongle; Wang, Qi; Sun, Keping; Feng, Jiang (Frontiers in Veterinary Science, 2021)
Chytridiomycosis is an amphibian fungal disease caused by Batrachochytrium dendrobatidis (Bd), which has caused large-scale death and population declines on several continents around the world. To determine the current status of Bd infection in amphibians, we conducted a global meta-analysis. Using PubMed, ScienceDirect, SpringerLink, China National Knowledge Infrastructure (CNKI) and Wanfang database searches, we retrieved a total of 111 articles from 2000 to 2021. Based on these, we estimated the Bd prevalence to be 18.54% (95% CI: 13.76-20.52) in current extent amphibians. Among these populations, the prevalence of Bd in Asia was the lowest at 7.88% (95% CI: 1.92-8.71). Further, no Bd infection was found in Vietnam. However, the prevalence of Bd in Oceania was the highest at 36.34% (95% CI: 11.31-46.52). The Bd prevalence in Venezuela was as high as 49.77% (95% CI: 45.92-53.62). After 2009, the global Bd prevalence decreased to 18.91% (95% CI: 13.23-21.56). The prevalence of Bd in epizootic populations was significantly higher than enzootic populations. The highest prevalence of Bd was detected with real-time PCR at 20.11% (95% CI: 13.12-21.38). The prevalence of Bd in frogs was the highest at 20.04% (95% CI: 13.52-21.71), and this different host was statistically significant (P < 0.05). At the same time, we analyzed the geographic factors (longitude, latitude, elevation, rainfall and temperature) that impacted the fungal prevalence in amphibians. Our meta-analysis revealed that factors including region, disease dynamic, detection method, host and climate may be sources of the observed heterogeneity. These results indicate that chytridiomycosis was a consistent threat to amphibians from 2000 to 2021. Based on different habitat types and geographical conditions, we recommend formulating corresponding control plans and adopting reasonable and efficient biological or chemical methods to reduce the severity of such diseases.